2016
DOI: 10.1177/1687814016656535
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on casing wear in highly deviated drilling for oil and gas

Abstract: Aimed at studying the casing wear in the highly deviated well drilling, the experimental study on the casing wear was carried out in the first place. According to the test data and the linear wear model based on the energy dissipation proposed by White and Dawson, the tool joint-casing wear coefficient was obtained. The finite element model for casing wear mechanism research was established using ABAQUS. The nodal movement of the contact surface was employed to simulate the evolution of the wear depth, exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…In general, the main variables that directly affect casing wear amount are the size of the casing and the drill pipe (DP), the grade of the drill pipe , the tool joint hardbanding material, the drilling speed, the applied side load, and the drilling fluid type and additives [4,5]. Huimei and Yishan [6] studied casing wear behavior in directional wells and discovered that the major factors that influence the casing wear are, the tool rotational speed, the rate of penetration, the drilling mud properties as well the well geometry [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the main variables that directly affect casing wear amount are the size of the casing and the drill pipe (DP), the grade of the drill pipe , the tool joint hardbanding material, the drilling speed, the applied side load, and the drilling fluid type and additives [4,5]. Huimei and Yishan [6] studied casing wear behavior in directional wells and discovered that the major factors that influence the casing wear are, the tool rotational speed, the rate of penetration, the drilling mud properties as well the well geometry [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have been conducted to quantify wear and estimate the wear factors under numerous conditions. Yu et al [6] investigated casing wear during oil well drilling at high deviation angle. Based on both experimental data and the wear model, the wear factor was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Doering et al [9] demonstrated that the new small-scale casing wear tester can produce wear mechanisms equivalent to both historical data produced by the DEA-42 test and from commercial down-hole service. Yu et al [10] developed an equation that relates the maximum wear depth to the residual casing strength after accumulative wear. Chen et al [11] examined the impact of drill string length, speed of rotation, direction of travel, and density of the drilling fluid on friction and they established a mathematical model to calculate the spacing of the friction reduction tool.…”
Section: Introductionmentioning
confidence: 99%
“…SAGD has been proven to be an effective heavy oil thermal recovery technology. [4][5][6] Figure 1 shows the method of implementing SAGD: a couple of horizontal wells with parallel horizontal sections are drilled at the bottom of the reservoir, the steam is injected into the upper horizontal well, the injected steam moves upward to form a steam chamber and continuously propagates upward and laterally to exchange the heat with oil, and the heated oil and the steam condensate are drained by the gravity to the lower production horizontal well and produced by artificial lift. Drilling SAGD wells needs to accurately control both horizontal sections, which are not only fixed at a spatial distance but also wholly extended in the reservoir sandstone.…”
Section: Introductionmentioning
confidence: 99%